"They Need More Training!" A National Level Analysis of Police Academy Basic Training Priorities. (December 2021) - Sloan, John J.; Paoline, Eugene A.
Recurring incidents of Black citizens killed or injured during interactions with police has led to calls for "more training" of officers, including new recruits. Prior research on academy-based police recruit training has centered on evaluation and heavily relied on case studies. The current study overcomes these limitations by analyzing the structure and content of academy-based basic training using secondary data collected from the population (N = 591) of U.S. police academies. Although we found significant mean differences across academies in total required contact hours needed to graduate and with how the hours were distributed across training areas, we also found academies adopted the same core curriculum consisting of six major "themes" and topics (n = 39) comprising them. We also found academies prioritized core areas of training in certain areas, while requiring far fewer hours in others. Implications of our results for basic training of recruits and suggestions for future research are then presented.